Javorov rak (Eutypella parasitica: Ascomycota: Fungi) na gorskem javorju in maklenu - Ogris, Nikica (Gozdarski vestnik, 2005)
Eutypella canker of maple is described, morphological characteristics of the disease on sycamore and field maple and the differences between the disease onthe two hosts are treated. The disease is provoked by the parasitic fungus Eutypella parasitica. Eutypella canker is an economically important disease ofseveral maple species in North America, where it is spread mostly in the surroundings of the Great Lakes in the USA and Canada. In Europe it was first found in Slovenia on sycamore maple. In this contribution field maple (Acer campestre L.) is reported as a new host for the fungus. The morphological characteristics of the disease on the two different hosts are very similar. The microscopic properties are the same. Slovenia as a country and its forestry profession hold the responsibility to eradicate or at least slow downthe spread of the disease in the natural area of maples, which comprises most of Europe.
Keywords: Acer campestre; Acer pseudoplatanus; Eutypella parasitica; javor; javorov rak; maklen; morfologija